KARAKTERISTIK DAN KONSEP MANAJEMEN MADRASAH - Sumarni, Weni; Iswantir, Iswantir; Simbolon, Ali Mustopa Yakub; Wijaya, Novri Agus Parta (Jurnal Manajemen Pendidikan, 2023)
This research is based because the productivity level of madrasas is still far from what was expected. Therefore this study aims to explain and describe the concept of madrasah management. The method used is library research (Library Research). The results of the study show that madrasah management has distinctive characteristics, namely, 1) having a strong vision and mission, 2) having charismatic and tough leadership 3) having open (transparent) management, 4) a religious learning environment 5) having continuous evaluation. The essence of madrasah-based management is to ensure that madrasahs have broad autonomy in managing resources, involve the community in management, and do not ignore national policies. By applying the principles of commitment, awareness and independence.